SOME ASPECTS OF ACCOUNTING SECURITY OF THE SUBSTANCE OF FINANCIAL RESULTS - Nagolyuk, Olena; Vasyurenko, Larysa; Shchebel, Andrii (РОЗВИТОК МІСТА, 2025)
In the conditions that have developed for the effective management of organizations, as well as for a deep analysis of the economic situation in the industry complex, the need to improve the quality, reliability and analytical value of information generated and provided by the accounting system is becoming increasingly relevant. This especially applies to one of the key evaluation indicators of the commercial activity of the enterprise – the financial result, which reflects the final efficiency of the activity and is an important basis for making management, investment and credit decisions. At the current stage of development of the economy and accounting science, there are a number of problems associated with the ambiguity of the interpretation of the term «financial result», differences in approaches to its calculation and interpretation in domestic and international practice. This, in turn, reduces the level of transparency of financial reporting and complicates the process of its analysis for a wide range of users – from enterprise management to external investors and regulatory authorities. Therefore, there is an objective need to improve the methodological principles of accounting for financial results, increase their analytical accuracy and adapt to modern business conditions. The article formulates a theoretical approach to a deeper understanding of the economic essence of the financial result as a key indicator of the efficiency of the enterprise, and also presents generally accepted methodological approaches to its definition, classification and calculation in the context of modern accounting practice; the classification of financial results is clarified, and its application in the accounting system is justified for the formation of additional profit indicators in reporting; a comparative characteristic of the methods for calculating the financial result in static and dynamic theories is analyzed. In modern conditions, a new type of risk – accounting risks – enters the management objects of business entities. The need to implement a risk-oriented accounting system is determined, which requires its separate reflection in reporting. В умовах, що склалися для ефективного управління організаціями, а також для глибокого аналізу економічної ситуації в галузевому комплексі, все більшої актуальності набуває необхідність підвищення якості, достовірності та аналітичної цінності інформації, що формується та надається системою бухгалтерського обліку. Особливо це стосується одного з ключових оцінних показників комерційної діяльності підприємства – фінансового результату, який відображає кінцеву ефективність діяльності та є важливою основою для прийняття управлінських, інвестиційних та кредитних рішень. На сучасному етапі розвитку економіки та облікової науки існує низка проблем, пов'язаних з неоднозначністю трактування терміна "фінансовий результат", відмінностями у підходах до його обчислення та інтерпретації у вітчизняній і міжнародній практиці. Це, своєю чергою, знижує рівень прозорості фінансової звітності та ускладнює процес її аналізу для широкого кола користувачів – від менеджменту підприємств до зовнішніх інвесторів і контролюючих органів. Тому виникає об'єктивна потреба у вдосконаленні методологічних засад обліку фінансових результатів, підвищенні їх аналітичної точності та адаптації до сучасних умов господарювання. У статті сформульовано теоретичний підхід до глибшого розуміння економічної сутності фінансового результату як ключового показника ефективності діяльності підприємства, а також представлено загальноприйняті методологічні підходи до його визначення, класифікації та обчислення у контексті сучасної облікової практики; уточнено класифікацію фінансових результатів, та обґрунтовано її застосування у системі бухгалтерського обліку для формування у звітності додаткових показників прибутку; проаналізовано порівняльну характеристику методик обчислення фінансового результату у статичній та динамічній теоріях. У сучасних умовах до об'єктів управління у суб'єктів господарювання потрапляє новий вид ризиків – бухгалтерські ризики. Визначено необхідність впровадження ризик-орієнтованої системи бухгалтерського обліку, що вимагає виокремленого його відображення у звітності.